Revitalisation of Godrej Appliances Division - Bhatta, N. M. K.; Mahapatra, Sabita, active 2017; Shankar, S. Bhavani (London : NeilsonJournals Publishing, 2017)
Godrej Appliance Division (GAD) was the first Indian company to manufacture and sell home appliances in Indian Markets. The success of Godrej was not challenged till 2000 due to limited competition in the markets. However, competition intensified with the entry of multinationals such as LG, Samsung, Whirlpool etc. Global presence and intensive research and development efforts enabled these companies to offer wider product portfolios compared to Godrej's select portfolio. Aggressive pricing, consumer and trade promotions along with branding efforts helped these multinational corporations capture the fast changing Indian market. By 2013, the competition became tougher and growth stagnated with industry witnessing high inflation, currency depreciation, commodity inflation, and tougher environmental regulations. All these compounding factors pushed Godrej into losses. Kamal Nandi took over as the business head of Godrej Appliances in early 2014 and his foremost task was to revitalize the business by adopting a multi-faceted strategy. This was aimed at fulfilling Godrej's vision to become one of the top three appliance companies in India by 2020. This case discusses strategies adopted by Kamal Nandi in achieving the turnaround by presenting several options which can be used for achieving the stated vision. The case emphasizes internal and external challenges while strategizing such turnarounds, the role of business model innovation in making it happen, as well as in the process of sustaining and accelerating growth.
Originally Published InBhatta, N. M. K., Mahapatra, S., & Shankar, S. B. (2017). Revitalisation of Godrej Appliances Division. Journal of International Business Education, 12(1), 341–352. JIBE12-0CS5.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Godrej Appliance Division -- Case studies; Business planning -- India -- Case studies; Strategic planning -- India -- Case studies